Magnetic Nanoparticles: Unravelling Magnetic Nanochain Formation in Dispersion for In Vivo Applications (Adv. Mater. 24/2021). Issue 24 (18th June 2021) - Nandakumaran, Nileena; Barnsley, Lester; Feoktystov, Artem; Ivanov, Sergei A.; Huber, Dale L.; Fruhner, Lisa S.; Leffler, Vanessa; Ehlert, Sascha; Kentzinger, Emmanuel; Qdemat, Asma; Bhatnagar‐Schöffmann, Tanvi; Rücker, Ulrich; et al.
Abstract : Spherical iron oxide nanoparticles in dispersion are controlled by external magnetic fields to form flexible and reversible chains for biomedical applications. In article number 2008683, Mikhail Feygenson and co‐workers combine the advanced scattering methods and reverse Monte Carlo simulations to directly visualize the chain formation in real space. This methodology paves the way for exploring novel assemblies of particles with a complex morphology in various liquid carriers.